Perceived trustworthiness of artificial intelligence implementation in Indonesia public sector services: Gen Z and Millennial perspectives - Aviandi Okta Maulana; Georgius Chandra Herfanda; Faradillah Hasan (Jurnal Akuntansi dan Auditing Indonesia, 2022)
Technological developments have an enormous impact on social and economic life, including the potential adoption of artificial intelligence in the public sector. This research focuses on perceived trustworthiness regarding the potential use of artificial intelligence in the public sector through the perceptions of the Millennial generation and Generation Z. Using a mixed-method through a Likert scale survey combined with open-ended questions, this research finds significant evidence that perceived trustworthiness is influenced by ability, benevolence, and integrity. The results of the open question analysis show that ability perception exists due to the following: perception of expertise in government institutions; benevolence due to the moral aspect to deliver public services; integrity which consists of two contrasting perspectives namely; first, positive feedback of trust toward government integrity, and second, negative feedback in questioning government integrity.